2011
DOI: 10.1016/j.jjcc.2011.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 1 receptor blocker attenuates diabetes-induced atrial structural remodeling

Abstract: Candesartan reduced CTGF expression and attenuated the fibrosis in diabetic rat atria. These results implied the protective effects of candesartan on diabetes-related atrial arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Candesartan significantly reduces expression of connective tissue growth factor and effectively suppresses the development of fibrotic deposition in diabetic rats [93]. Furthermore, candesartan reduces accumulation of AGEs and subsequent albuminuria by downregulating the nicotinamide adenine dinucleotide phosphate oxidase p47phox component and by inducing NO synthase expression, as well as by attenuating expression of RAGE in type 2 diabetic KK/Ta mouse kidneys [94].…”
Section: Hmgb1/rage and Risk Factors Of Strokementioning
confidence: 99%
“…Candesartan significantly reduces expression of connective tissue growth factor and effectively suppresses the development of fibrotic deposition in diabetic rats [93]. Furthermore, candesartan reduces accumulation of AGEs and subsequent albuminuria by downregulating the nicotinamide adenine dinucleotide phosphate oxidase p47phox component and by inducing NO synthase expression, as well as by attenuating expression of RAGE in type 2 diabetic KK/Ta mouse kidneys [94].…”
Section: Hmgb1/rage and Risk Factors Of Strokementioning
confidence: 99%
“…Several studies indicate that RAA inhibition suppresses the expression of RAGE and connective tissue growth factor (CTGF) as well as AGE formation [68][69][70][71][72]. In streptozotocin-induced diabetic rats Kato et al demonstrated that treatment with candesartan reduces CTGF expression and effectively suppresses the development of atrial fibrotic deposition [73]. The attenuation of CTGF expression by candesartan may be derived via decreased AGE interaction with RAGE and/or from a direct effect of the drug [73].…”
Section: Upstream Therapies For Diabetes Mellitus Related Atrial Remomentioning
confidence: 99%
“…Early studies identified Ang II and its signaling effectors as potential culprits for triggering LV hypertrophy (LVH), fibrosis and cardiac remodeling; but many studies are now supporting at least a synergistic role for aldosterone in the pathogenesis of cardiac fibrosis observed as a result of the diabetes-induced metabolic impairment (19,26,41,55,70,97,106). These observations are also supported by the fact that the serum levels of aldosterone have been found to be increased in the pre-diabetic and diabetic conditions and contribute to the LVH and cardiac fibrosis seen in these conditions (26,106).…”
Section: Development and Progression Of Cardiac Dysfunction As A Resumentioning
confidence: 99%